Integração ensino serviço na formação de enfermeiros na estratégia saúde da família - Silva, Durcival Francisco da (2013)
This is a descriptive and exploratory case study with a cross and quantitative approach, which aimed to identify the integration process in the Education Service of nursing training in the Family Health Strategy. Data collection was performed by using a semi-structured questionnaire with a population of 60 participants and analyzed by simple statistics. In the results, we identified several difficulties and negative points in the training of these professionals. Among the positive points, stands out the inclusion of students in these services which leads to better training and these participating subjects know the features and aspects required for this training. It is concluded that frailties should be worked in the education and work world, should be conducted a continuing education, reinforcing the importance, potential and opportunities of learning service integration, and the need of training nurses to attend the demands of health system as well as enhancing the nursing category.